Experimental investigation of temperature rise in bone drilling with cooling: A comparison between modes of without cooling, internal gas cooling, and external liquid cooling. (January 2018) - Shakouri, Ehsan; Haghighi Hassanalideh, Hossein; Gholampour, Seifollah
Bone fracture occurs due to accident, aging, and disease. For the treatment of bone fractures, it is essential that the bones are kept fixed in the right place. In complex fractures, internal fixation or external methods are used to fix the fracture position. In order to immobilize the fracture position and connect the holder equipment to it, bone drilling is required. During the drilling of the bone, the required forces to chip formation could cause an increase in the temperature. If the resulting temperature increases to 47 °C, it causes thermal necrosis of the bone. Thermal necrosis decreases bone strength in the hole and, subsequently, due to incomplete immobilization of bone, fracture repair is not performed correctly. In this study, attempts have been made to compare local temperature increases in different processes of bone drilling. This comparison has been done between drilling without cooling, drilling with gas cooling, and liquid cooling on bovine femur. Drilling tests with gas coolant using direct injection of CO2 and N2 gases were carried out by internal coolant drill bit. The results showed that with the use of gas coolant, the elevation of temperature has limited to 6 °C and the thermal necrosis is prevented. Maximum temperature rise reached in drilling without cooling was 56 °C, using gas and liquid coolant, a maximum temperature elevation of 43 °C and 42 °C have been obtained, respectively. This resulted in decreased possibility of thermal necrosis of bone in drilling with gas and liquid cooling. However, the results showed that the values obtained with the drilling method with direct gas cooling are independent of the rotational speed of drill.